Polaryzacja czy wyrównywanie szans rozwoju gospodarczego w regionach Polski - Gaczek, Wanda Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of the article is to explain how disparities in the level of economic development of Poland's subregions changed between 2000 and 2002. The analysis was made on the basis of a synthetic indicator of growth (the sum of standardized variables). The results show that the economic growth of the subregions in metropolitan voivodships improved more significantly than that in non-metropolitan subregions. A characteristic feature was a decline in the value of the synthetic indicator of growth in large cities and an increase of this indicator in some subregions surrounding a metropolis. The lowest negative indicators of growth were still in the subregions of the eastern voivodships of Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 23-37